Investigation of Fish Consumption in Giresun City - Mustafa Türkmen; Aysun Türkmen; Köksal Duran (Turkish Journal of Agriculture: Food Science and Technology, 2016)
This study aimed to investigate the fish consumption in Giresun by survey method. Fish meat was compared with other meat types according to education, level of income, consumption rate and quantity. In research carried out according to the random sampling method. Questions were asked face to face a total of 433 persons. A total 428 participants (98.9%) stated that they consumed fish. However, the most consumed meat type is chicken, second is fish. A total 91% participant preferred marine fish. The most consumed fish species is anchovy with 34%. Fish consumption per person in Giresun is above Turkey’s average with 12.34 kg/year.